The Role of Media and Communication Channels in the Socialization of the Mimika Smart City Program - Biru, Magdalena Charlan; Arifin, Pupung (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The smart city concept has been introduced since the 1990s, even since 2010, the European Commission has launched a smart city initiative document. In response to these global needs and challenges, in 2017, the Ministry of Communication and Information Technology has determined 24 regencies/cities in Indonesia to be the initial pilot of smart city implementation in Indonesia. Mimika Regency was chosen to be one of the regions that realize the 100 Smart City cities/regencies movement in Indonesia. One way that the objectives of the smart city are met is by the socialization strategy carried out by the Mimika Regency Regional Government to the Mimika community. This article uses a qualitative descriptive approach with interview techniques. Interviews were conducted with the Communication and Informatics Office (Diskominfo) and the Mimika Regional Apparatus Organization (OPD). The results of the research obtained are the Regional Government of Mimika Regency, in this case the Communication and Informatics Office (Diskominfo) and the Regional Apparatus Organization (OPD) have not implemented a socialization strategy according to the concept of a socialization strategy. However, the Mimika Regional Government has its own socialization strategy in conducting socialization about Mimika Smart City.